OPTIMALISASI PENGADAAN MAKANAN SEHAT DALAM PEMENUHAN GIZI SEIMBANG PADA ANAK DI RA MAMBA’UL HUDA JAMBESARI PONCOKUSUMO-MALANG - Dewi Umniyah; Evi Nurhalimah (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2022)
Procurement of healthy food in schools aims to maintain health, especially in children's intelligence. There are foods that are sold without paying attention to the nutritional side. The purpose of this study was to describe the provision of healthy eating in terms of the nutritional content of children in a balanced manner. The research method uses descriptive-qualitative with the type of study cassus research. The results showed that the procurement of healthy food has 4 stages, namely preparation of coordinating food prices that are economical, healthy and can make children taste good. Implementation can pay attention to the rules before starting to eat together. Supervision is carried out when preparing and managing food related to its nutritional content and evaluating assessments related to nutritional content including carbohydrates, proteins, fats, vitamins, and minerals which are coordinated at a monthly meeting. Suggestions made by parents can be to prepare healthy food supplies. As well as, the sorting of natural food ingredients and nutritional content in an organized manner.